(untitled) (Gestión y Gerencia, 2021)
The article shows part of a research that aimed to generate a praxological ontoepistemic substrate of educational management knowledge, from the essence of wisdom. The volunteer versionants in the study were four head teachers from the Arístides Bastidas School Municipality, Yaracuy State. The investigative didactics follows the orientation of the quadripolar model of Rusque (2001). In this way, the methodology of scenarios according to Hevia (2001) is referenced for the creation of praxology through strategies, situations and contexts in four binding scenarios. This is a integrative level field research, discourse analysis was used to the questionnaire as well as negotiation, work tables and reflective meeting of managerial knowledge. Validity and reliability were expressed in systematic feedback and triangulation of sources. It was concluded that educational managers emerge to a position valued in the underlying being from a deep reflection, from the spirit.